An observational descriptive study on the incidence, severity and outcome of different etiological varieties of acute pancreatitis in a rural based teaching hospital - Nandy, Sagnik; Mondal, Debashis; Biswas, Arnab (International Journal of Research in Medical Sciences, 2023)
Background: According to the 1992 Atlanta Symposium, acute pancreatitis (AP) is defined as an acute inflammatory process of the pancreas that may also involve peripancreatic tissues and remote organ systems. Methods: It was an observational descriptive study. The study was from May 2012 to April 2013. The study was undertaken in the department of General Surgery of Burdwan Medical College and Hospital. Results: In this study, we found that alcohol was the most common etiological factor present in 48.57% of patients, whereas gallstones come second being present in 31.42% cases. Among Indian studies, one found 60% cases being gallstone induced, while another found alcoholism as the most common cause. The study that found alcoholism as the most common cause of acute pancreatitis was also from Eastern India (West Bengal, to be precise). In our study, 17.14% cases of acute pancreatitis had to be classified as idiopathic pancreatitis, as no readily identifiable cause was found. In most series, 10-25% cases are found to be idiopathic. From results, it is seen that most cases of acute pancreatitis tend to occur in the age group 41-50 yrs (40%) followed by 31-40 yrs (34.28%). Conclusions: This study was done to estimate the incidence of different etiological varieties of acute pancreatitis, to estimate the incidence of mild and severe acute pancreatitis and accordingly necessity for CT scan, to estimate the outcome in terms of cure, recurrence, morbidity and mortality. 35 patients of acute pancreatitis were enrolled for the study.